Birth prevalence of congenital heart disease among newborns in a tertiary hospital in Benin City, Nigeria - Sadoh, Wilson; Okonkwo, Ikechukwu; Okonkwo, Chukwunwendu A. (CARDIOVASCULAR JOURNAL OF AFRICA, 2021)
Background: Congenital heart disease (CHD) is an important cause of childhood morbidity. The birth prevalence and distribution of CHD among neonates in a tertiary hospital in Nigeria was determined. Methods: This descriptive, cross-sectional study involved consecutive neonates in the neonatal and postnatal wards of the hospital. Bedside echocardiography was conducted on all neonates. Data entry and analysis was done with IBM-SPSS version 20.0. Results: A total of 2849 neonates were recruited, consisting of 1482 (52.0%) males. Forty-one neonates had CHD, giving a birth prevalence of 14.4/1 000 live births. Of the 41 with CHD, 21 (51.2%) were male. Thirty-six (87.8%) neonates had acyanotic CHD, of which the commonest was isolated ventricular septal defect [11 (26.8%)]. Transposition of the great arteries [3 (7.3%)] was the commonest cyanotic CHD. Conclusions: The birth prevalence of 14.4/1 000 live births in this study is high and buttresses the need for strengthening existing cardiac services in Nigeria.
ACE: Reproductive Health Innovation
Keywords: ACE: Reproductive Health Innovation; University of Benin; Nigeria; CERHI; Fidelis E. Eki-udoko; Ezinne Emerruwa; Congenital Heart Disease; Echocardiography; Neonates